Cutting process statement identification using the termovoltage of tool work thermocouple - Milikić, Dragoje; Gostimirović, Marin; Kovač, Pavel (Journal of Production Engineering, 2023)
The paper presents the development of an automatic measurement system for the thermovoltage of a tool-work thermocouple and its possibilities for identifying the process state. Verification of the realized measuring system was conducted during the thermovoltage measurement of the tool-work thermocouple and tool wear measurement. The relationship between tool life and thermovoltage was also determined